Inverter power supply device - CUI DEYOU; CAO JINHU; MEI XIAODONG (2013)
The invention discloses an inverter power supply device which is used for converting a direct current output by a direct current power source into alternative current. The inverter power supply device comprises a front level current feed circuit and a rear level inverter circuit. The front level current feed circuit comprises a full-bridge converter, an isolation transformer and a rectifying circuit, wherein the full-bridge converter, the isolation transformer and the rectifying circuit are sequentially connected in series. The rear level inverter circuit is a single buck inverter circuit. According to the inverter power supply device, under the condition that energy conversion efficiency is ensured, complexity of control can be reduced, and convenience is brought to reactive power regulation and power dilatation.